MASS MEDIA OF THE KAZAKH ASSR AND SOCIO-POLITICAL ACTIVITY OF ZHUSUPBEK AIMAUYTULY (Journal of history, 2023)
There were fundamental changes in the Kazakh steppe after the formation of Soviet statehood. New reforms were carried out. Socio-political life gradually began to stabilize and the first steps were taken to strengthen the socio-economic situation in the country. The entire Kazakh intelligentsia took part in it. The figures of the former Alash Horde worked almost entirely in the Soviet system. One of them was Zhusipbek Aimauytuly. In turn, Zhusipbek Aimauytuly, like all Alashordin residents, was forced to recognize the new Soviet system, engage in socio-political life and contribute to solving state tasks for the prosperity of the country.The article describes the socio-political activities, creativity and career of Zhusipbek Aimautuli in the Soviet period. Archival materials and historical and source studies conducted on the sources of the printed publication say that he, as a statesman and public figure, urged young people to be responsive citizens who love their people, and also paid great attention to social issues.Keywords. Newspaper, editor, commissariat of public education, government, archive, communist party, education.